Endogenous and exogenous porphyrins as photosensitizers in the hep-2 human carcinoma cell line - Alvarez, M G; Milanesio, M; Rivarola, V; Durantini, E; Batlle, A; Fukuda, H (Cellular and Molecular Biology, 2009)
The photodynamic activity of three photosensitizers (PS): ALA-induced PPIX, the porphyrin derivative 5-(4-trimethylammoniumphenyl)-10, 5, 20-tris (2,4,6- trimethoxyphenyl) porphyrin (CP) and the molecular dyad porphyrin-C60 (P-C60), the last two incorporated into liposomal vesicles, was evaluated on Hep-2 human larynx carcinoma cell line. ALA-induced accumulation of the endogenous PS PPIX, reached saturation values between 5 and 24 h incubation time; the maximal PPIX content was 5.7 nmol/106 cells. The same intracellular level was accumulated when the cationic porphyrin CP was used, while the amount of P-C60 attained was 1.5 nmol/106 cells. Under violet-blue exciting light, the fluorescence of PPIX and P-C60 was found in the cytoplasm showing a granular appearance indicating lysosomal localization. CP was mainly detected as a filamentous pattern characteristic of mitochondrial localization. No dark cytotoxicity was observed using 1mM ALA, 5 Î¼M CP and 1 Î¼M P-C60 after 24 h incubation. Cell morphology was analyzed using Hoechst-33258, toluidine blue staining, TUNEL assay and DNA fragmentation, 24 h after irradiation with 54 J/cm2. When photosensitized with ALA and P-C60, chromatine condensation characteristic of apoptotic cell death was found; instead, 58 % of necrotic cells were observed with CP. The results show that in the Hep-2 cells, of the three PS analyzed, the molecular dyad P-C60 was more efficient than CP and PPIX, and confirm that PDT can induce different mechanisms of cell death depending on the PS and the irradiation dose.